The household and military retinue of Edward the Black Prince - Green, David S. (1998)
The household and military retinue of Edward the Black Prince (1330-1376) was created in the early years of the Hundred Years W ar. This thesis examines the role which the retinue played in that conflict and how the administration of the prince's estates contributed to that effort through the provision of troops, supplies and finance. It aims to place the Black Prince and his retainers annuitants and servants in a national context, investigating their role in the Hundred Years War and A nglo-Gascon political society, whilst also highlighting the individual and collective roles that they played in the prince's retinue. It also demonstrates something of the atmosphere evident within the household through the examples of the chivalric ethic and religious attitudes.These elements are also seen in the links that existed between members of the retinue and household that were created by their common service to the Black Prince but also through a variety of other associations ,familial, financial,political and geographical. The particular status of the heir-apparent governed the nature of his retinue and comparisons are drawn with the other great bastard feudal a ssociations of the day, particularly the royal household and the Lancastrian affinity. The thesis concludes with a biographical appendix, which highlights certain careers and summarises those of others with a wide range of links to the Black Prince.